2011
DOI: 10.1007/s00774-011-0287-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin K on bone mineral density: a meta-analysis of randomized controlled trials

Abstract: A number of randomized controlled trials (RCTs) examining the role of vitamin K on bone mineral density (BMD) have yielded inconsistent results. We performed a meta-analysis of these trials to assess the effect of vitamin K on BMD. We searched MEDLINE, EMBASE and CENTRAL for relevant studies of RCTs examining the role of vitamin K on BMD. Data on participants, interventions, and outcomes were extracted and the quality of all included trials assessed. Primary outcomes for analysis were absolute changes in BMD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 44 publications
2
58
0
3
Order By: Relevance
“…Clinical meta-analyses have previously revealed that supplementation with vitamin D and vitamin K resulted in increased bone mineral density at the femoral neck and lumbar spine, respectively [48], which agrees with the significant increase in mineralization we observed using supplementation with vitamin D and K. Similar to our meta-analyses, the results of both of these studies must be treated with caution due to heterogeneity. However, we observed variable results of the effects of these vitamins on parameters indicative of bone formation depending on the type of cells used, which calls into question the use of particular cell lines and animal models to test drugs/supplements as a precursor to clinical studies.…”
Section: Figuresupporting
confidence: 91%
“…Clinical meta-analyses have previously revealed that supplementation with vitamin D and vitamin K resulted in increased bone mineral density at the femoral neck and lumbar spine, respectively [48], which agrees with the significant increase in mineralization we observed using supplementation with vitamin D and K. Similar to our meta-analyses, the results of both of these studies must be treated with caution due to heterogeneity. However, we observed variable results of the effects of these vitamins on parameters indicative of bone formation depending on the type of cells used, which calls into question the use of particular cell lines and animal models to test drugs/supplements as a precursor to clinical studies.…”
Section: Figuresupporting
confidence: 91%
“…Several recent meta-analyses and reviews of the effects of vitamin K supplementation show a positive effect on BMD and indices of bone strength, with reduced fracture incidence in mainly postmenopausal women; the majority of long-term trials supplemented MK4 to Japanese 8,69,70 . A subsequent study confirmed the beneficial effect of vitamin K1 supplementation on BMD in postmenopausal women, with doses of 80mcg/d phylloquinone proving effective 66 .…”
Section: Bonementioning
confidence: 99%
“…Each patient were either given vitamin K2 (in ten trials, eight of them were supplemented with MK-4 15-45 mg/ day and two with MK-7 0.2-3.6 mg.day) or vitamin K1 (in seven trials 0.2-10 mg/day) supplements (6). After 6 to 36 months of vitamin K supplementation, no significant increase of BMDs was observed in patients' femoral necks, but the average BMDs of the patient's' lumbar spines increased by 1.3% (6) .…”
Section: What Do the Research Clinical Trials Say About Vitamin K Effmentioning
confidence: 99%
“…Each patient were either given vitamin K2 (in ten trials, eight of them were supplemented with MK-4 15-45 mg/ day and two with MK-7 0.2-3.6 mg.day) or vitamin K1 (in seven trials 0.2-10 mg/day) supplements (6). After 6 to 36 months of vitamin K supplementation, no significant increase of BMDs was observed in patients' femoral necks, but the average BMDs of the patient's' lumbar spines increased by 1.3% (6) . Specifically, patients given vitamin K2 treatments experienced a significant 1.8% increase in their average lumbar spine BMDs, while patients treated with vitamin K1 supplements did not experience the same significant increases in their average BMDs (6) .…”
Section: What Do the Research Clinical Trials Say About Vitamin K Effmentioning
confidence: 99%